Hubungan antara keterampilan berpikir kritis dan metakognisi dengan penguasaan konsep pada beberapa model pembelajaran Kimia - Muhammad Danial; Taty Sulastri (Seminar Nasional LP2M UNM, 2019)
This study aims to explain the relationship between critical thinking skills (CTS) and mastery of concepts and the relationship between meta-cognition and mastery of concepts in several chemistry learning models in senior high school. The learning models used in this study are discovery learning and direct instruction. This research was carried out for 8 months at Senior High School Makassar city and Maros Regency by involving two graduate program students in the S2 chemistry education study program. The subject and object of this study were XI MIA SMA class students for buffer solution chemistry. The research tools and instruments used in this learning study are instructional tools and test instruments of critical thinking skills and mastery tests of concepts and instruments of the Meta-cognitive Awareness Inventory. The methods used are 1) observation, 2) preparation of teaching tools, 3) preparation of assessment instruments,4) implementation of learning in schools, 5) filling questionnaires, CTS tests, and mastery of concept tests. Data were analyzed inferentially and descriptively. The results of data analysis show that (1) there is a relationship between critical thinking skills and mastery of chemistry concepts for students both learned by investigation-based learning models (discovery learning) or those taught with direct instruction model, (2) there is no relationship between meta-cognition and mastery students 'chemistry concepts both learned by investigation-based learning models (discovery learning) as well as those taught with direct instruction models, and (3) critical thinking skills and mastery of chemistry’s concepts that learned by investigation-based learning models are higher than those taught by models direct instruction.